Dilute Alkali and Hydrogen Peroxide Treatment of Microwave Liquefied Rape Straw Residue for the Extraction of Cellulose Nanocrystals. (19th February 2017) - Huang, Xingyan; De Hoop, Cornelis F.; Li, Feng; Xie, Jiulong; Hse, Chung-Yun; Qi, Jinqiu; Jiang, Yongze; Chen, Yuzhu
Abstract : Microwave-assisted liquefaction of rape straw in methanol was conducted to collect the liquefied residues for the extraction of cellulose nanocrystals (CNCs). The liquefied residue with content of 23.44% from 180°C/7.5 min was used to fibrillate CNCs with dilute alkali (2% NaOH) and hydrogen peroxide (5% H2 O2 ) treatments, followed by ultrasonication for 15 min. The FT-IR spectra and SEM images revealed that the liquefied residue from 180°C/7.5 min exhibited a relatively homogeneous texture and a huge surface with cellulose as core structure. The retained hemicelluloses and other impurities in the liquefied residue were eliminated by 2% NaOH treatment, and the surface and accessibility of the alkali treated sample were significantly increased by 5% H2 O2 treatment. The TEM images confirmed the CNCs had an average diameter of 12.59 nm. The CNCs had good thermal stability with a maximum weight loss temperature of 376.5°C.